The Value of Pre-Screening in the Alzheimer's Prevention Initiative (API) Autosomal Dominant Alzheimer's Disease Trial (2018)
ABSTRACT: The Alzheimer's Prevention Initiative (API) Autosomal Dominant Alzheimer's Disease (ADAD) trial evaluates the anti-amyloid-β antibody crenezumab in cognitively unimpaired persons who, based on genetic background and age, are at high imminent risk of clinical progression, and provides a powerful test of the amyloid hypothesis. The Neurosciences Group of Antioquia implemented a pre-screening process with the goals of decreasing screen failures and identifying participants most likely to adhere to trial requirements of the API ADAD trial in cognitively unimpaired members of Presenilin1 E280A mutation kindreds. The pre-screening failure rate was 48.2%: the primary reason was expected inability to comply with the protocol, chiefly due to work requirements. More carriers compared to non-carriers, and more males compared to females, failed pre-screening. Carriers with illiteracy or learning/comprehension difficulties failed pre-screening more than non-carriers. With the Colombian API Registry and our prescreening efforts, we randomized 169 30-60 year-old cognitively unimpaired carriers and 83 non-carriers who agreed to participate in the trial for at least 60 months. Our findings suggest multiple benefits of implementing a pre-screening process for enrolling prevention trials in ADAD.